2016
DOI: 10.1097/gme.0000000000000569
|View full text |Cite
|
Sign up to set email alerts
|

Use of hormone therapy and isoflavones and mammographic density in Spain

Abstract: Our results show a low prevalence of HT and isoflavone use in postmenopausal Spanish women. In this population, HT use was not associated with mammographic density, whereas some categories of isoflavone users had higher density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…However, these single chemicals contributed little to the total xenoestrogen burden in the women in this study and can hardly explain the observed regional variations. Navarra is also one of the regions in Spain with a higher than average prevalence of postmenopausal hormone therapy use ( Isidoro et al 2015 ), but our study found no differences in TEXB-α or TEXB-β levels between never and ever users of hormone therapy. Thus, larger population-based studies are required to identify determinants of serum TEXB levels that contribute to their geographical distribution.…”
Section: Discussioncontrasting
confidence: 72%
“…However, these single chemicals contributed little to the total xenoestrogen burden in the women in this study and can hardly explain the observed regional variations. Navarra is also one of the regions in Spain with a higher than average prevalence of postmenopausal hormone therapy use ( Isidoro et al 2015 ), but our study found no differences in TEXB-α or TEXB-β levels between never and ever users of hormone therapy. Thus, larger population-based studies are required to identify determinants of serum TEXB levels that contribute to their geographical distribution.…”
Section: Discussioncontrasting
confidence: 72%
“…Genistein and daidzein may also be growth factors for human estrogen-dependent tumor cells, both in vitro (Carreau, Flouriot, Bennetau-Pelissero, & Potier, 2009) and in animal models of xenograft nude mice (Du et al, 2012). Similarly, soy isoflavones demonstrated alteration in the mammary density in Western postmenopausal women (Isidoro et al, 2016).…”
Section: Adverse Effects Of Phytoestrogensmentioning
confidence: 99%
“…Since then, several studies have shown controversial results in either the beneficial or adverse effects of phytoestrogen. Regarding the adverse effects of isoflavones, it would seem reasonable to return to traditional Asian exposure levels rather than supplementation to favor the positive health effects of isoflavones (Isidoro et al, 2016).…”
Section: Adverse Effects Of Phytoestrogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancient studies also showed that soy food had estrogenic and proliferative effects on healthy breast cells in premenopausal women [ 125 ]. Equally, soy isoflavones have been shown to increase the mammary density in Western, post-menopausal women [ 126 ]. To help with the interpretation of such controversial results, it should be noted that existing studies most probably underestimate soy and isoflavone intake, not considering hidden isoflavones from manufactured foodstuffs.…”
Section: Beneficial Effectsmentioning
confidence: 99%